Random fixed points of weakly inward operators in conical shells. (1995) - Beg, Ismat; Shahzad, Naseer
Abstract : Conditions for random fixed points of condensing random operators are obtained and subsequently used to prove random fixed point theorems for weakly inward operators in conical shells.